Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fnmol.2018.00410
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Layer 5 Intratelencephalic Projection Neurons From the Mature Mouse Motor Cortex

Abstract: The mature cortex contains hugely diverse populations of pyramidal projection neurons (PNs), critical to normal forebrain circuits. In order to understand the healthy cortex, it is essential to characterize this neuronal complexity. We recently demonstrated different identities for Fezf2-positive (Fezf2+ve) and Fezf2-negative (Fezf2−ve) intratelencephalic-PNs (IT-PNs) from layer 5 of the motor cortex (M1). Comparatively, each IT-PN type has a distinct electrophysiological phenotype and the Fezf2+ve IT-PNs disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The role of CSF-2 as a major mediator of ALSP pathology was recently established by demonstrating that deletion of a single Csf2 allele in ALSP mice prevented development of the behavioral deficits, normalized most pathologies and partially restored the changes in the microglial transcriptome (Chitu et al, 2020). However, since cortical layer V neurons are gradually lost in ALSP mice and a proportion of these neurons express the CSF-1R (Chitu et al, 2015;Clare et al, 2018), we investigated whether decreased CSF-1R expression could affect neuronal survival independently of its effect on microglial functions. While at present it is unclear whether How might Csf1r +/− microglia mediate the selective loss of layer V neurons?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of CSF-2 as a major mediator of ALSP pathology was recently established by demonstrating that deletion of a single Csf2 allele in ALSP mice prevented development of the behavioral deficits, normalized most pathologies and partially restored the changes in the microglial transcriptome (Chitu et al, 2020). However, since cortical layer V neurons are gradually lost in ALSP mice and a proportion of these neurons express the CSF-1R (Chitu et al, 2015;Clare et al, 2018), we investigated whether decreased CSF-1R expression could affect neuronal survival independently of its effect on microglial functions. While at present it is unclear whether How might Csf1r +/− microglia mediate the selective loss of layer V neurons?…”
Section: Discussionmentioning
confidence: 99%
“…This could be a consequence of loss of microglial homeostatic functions. However, since previous studies (Luo et al, 2013) reported that CSF-1R signaling mediates neuronal survival cell autonomously and a subpopulation of layer V neurons express Csf1r (Chitu Clare et al, 2018), it is also possible that the reduced survival of layer V neurons is mediated by loss of direct regulation by the CSF-1R. Analysis of cortical neurons showed that MCsf1r het , but not NCsf1r het mice, reproduced the loss in layer V neurons (Figure 4a,b), indicating that these cells are lost due to microglial dysfunction.…”
Section: Microglial But Not Neural Lineage Csf1r Heterozygosity Promentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to microglia, in the brain, CSF-1R is also expressed by neural progenitor cells, and subpopulations of neuronal cells [21][22][23][24]. While the functional significance of CSF-1R expression in neurons at steady state remains unclear, studies in vitro suggest that CSF-1R signaling in neural progenitor cells suppresses proliferation, enhances their neuronal differentiation and promotes the survival of their early progeny [22].…”
Section: Accepted Articlementioning
confidence: 99%
“…Efforts to describe these changes are limited to alterations in input or output specificity between interneurons and principal cells (Lee et al, 2016;Lu et al, 2014;Trouche et al, 2013) or laminar specific adaptations (Koester and Johnston, 2005;Sjöström and Häusser, 2006). L5 neurons have been categorized by their electrophysiological properties (Shai et al, 2015), connectivity (Hattox and Nelson, 2007), morphology (Oswald et al, 2013), location (Lefort and Petersen, 2017) and gene expression (Clare et al, 2018;Tasic et al, 2016). These cortical output neurons send long-range projections throughout the brain and are thus optimally situated to integrate columnar information (Baker et al, 2018;Koester and Johnston, 2005;Sjöström and Häusser, 2006) and effect widespread adaptations (Feldmeyer, 2012;Grillner et al, 2005;Petersen, 2019).…”
Section: Introductionmentioning
confidence: 99%